RELATIONSHIP BETWEEN DURATION OF DRUGS CONSUMPTION AND PHYSICAL FITNESS LEVELS WITH COGNITIVE FUNCTION TO REHABILITATION PATIENT AT ERNALDI BAHAR HOSPITAL - Retno Rianto (Sriwijaya University Learning and Education International Conference, 2018)
Drugs (Narcotics, Psychotropic, and other addictive substances) can harm human life, if consumed in an inappropriate manner, can even cause death. Drugs have a very wide negative impact; both physically, psychologically, economically, socially and culturally and so forth. Drugs cause dependence causing physical and psychic dependence, this situation will make the lazy to move and think resulting in decreased fitness and cognitive function. The design of this study is cross sectional with the number of samples of 7 people. The results of this study indicate a relation between duration of drug consumption and physical fitness level with cognitive function in drug rehabilitation patients at Ernaldi Bahar Hospital (ρ = 0,000; α = 0,05). In addition, this study is expected to increase human knowledge of drugs so as to avoid drug abuse.